Anatomy of Subpancreatic Transverse Colon Vessel and Its Clinical Significance: An Observational Study - Liao, Jiankun; Qin, Haiquan; Wei, Li; Huang, Zigao; Meng, Linghou; Wang, Wentao; Mo, Xianwei (Frontiers in Surgery, 2022)
Purpose To observe and count the probability of presence and the anatomy of the vessel arising via the inferior margin of the pancreas and traveling within the transverse mesocolon, and analyze its clinical significance. Methods Patients who underwent radical operation for transverse colon cancer or descending colon cancer from January 2020 to November 2021 and a nonspecific cadaver were included in this study. We observed and recorded intraoperatively for the probability of presence and the anatomy of the vessel arising via the inferior margin of the pancreas and traveling within the transverse mesocolon. And its property was determined by tissue slice. Results A total of 84 patients were included, of which, the vessel was observed in 72 (85.7%) patients, and its property was confirmed by tissue slice of one patient after surgery. The vessel was also observed in a nonspecific cadaver. Originating from transverse pancreatic artery, often one, occasionally two, rarely three vessels arose via the inferior margin of pancreas and supplied the left transverse colon. Artery and vein parallel ran, and it was difficult to separate them due to their small diameter, but the vessels may thicken under certain conditions for increasing blood supply. Conclusion The vessel, which is not yet reported and named in the literature, can be called the subpancreatic transverse colon vessel, which has a high probability of presence in humans and may be of great significance to human physiological anatomy, surgery, and oncology, and deserves recognition and attention from surgeons.